The Existence of Radio Republik Indonesia Banda Aceh in Educating Disaster Risk Reduction Efforts - Maisarah, Mila; Ismail, Nazli; Munadi, Khairul (Jurnal The Messenger, 2021)
Radio is one of the media still used by the public either for having entertainment or gaining information. Amid the rapid growth of television and internet, radio is still exhibiting its existence. Radio s involvement on the efforts of educating Disaster Risk Reduction (DRR) to the public is crucial because it can be accessed conveniently in variety circumstances. This study focused on examining how the existence of Radio RepublikIndonesia (RRI) Banda Aceh in educating DRR efforts for the public. It discussed about how the people obtain the DRR education through some radio programs concerning to DRR. RRI Banda Aceh was chosen because it is the only one government owned radio in Banda Aceh that is responsible on educating the public through the broadcasting contents. This study was conducted by using a qualitative method. The data were collected by means of interviewing the leaders of RRI Banda Aceh and observing the recording of the radio broadcasted contents related to the DRR. This study, eventually, found that the existence of RRI Banda Aceh in educating DRR efforts was manifested in three different ways such as broadcasting disaster news, talk-shows, and public service announcements. Those three ways had their own advantages and disadvantages.